Polymorphisms at the Ligand Binding Site of the Vitamin D Receptor Gene and Osteomalacia. Issue 4 (9th June 2013) - Ak, Duygu Gezen; Kahraman, Hakkí; Dursun, Erdinç; Duman, Belgin Süsleyici; Erensoy, Nevin; Alagöl, Faruk; Tanakol, Refik; Yılmazer, Selma
Abstract : Vitamin D receptor (VDR) gene polymorphisms have been suggested as possible determinants of bone mineral density (BMD) and calcium metabolism. In this study, our aim was to determine whether there is an association between VDR gene polymorphism and osteomalacia or not. We determined ApaI and TaqI polymorphisms in the vitamin D receptor gene in 24 patients with osteomalacia and 25 age-matched healthy controls. Serum calcium, phosphorus, ALP, PTH, 25OHD levels were also examined. We used PCR and RFLP methods to test for an association between osteomalacia and polymorphisms within, intron 8 and exon 9 of the VDR gene. When the control and patients were compared for their ApaI and TaqI genotypes there was no relationship between VDR gene allelic polymorphisms and osteomalacia. Whereas a nearly significant difference for A allele was found in the allellic distribution of the patients ( p = 0.08). Also no association between biochemical data and VDR gene polymorphisms was observed.